ХИЙЎА ХАНЛЫҒЫ ТАРИЙХЫН ҮЙРЕНИЎДЕ МУНИС ҲӘМ АГАҲИЙ ШЫҒАРМАЛАРЫНЫҢ ӘҲМИЙЕТИ - Тлеўмуратов, М.; Юсупов, К.А. (FAN va JAMIYAT, 2017)
The article deals with the role of works of Munis and Ogahiy in the study of history of Central Asia. There is detailed information about the life and creation of Munis and Ogahiy in the article. The article also contains the data about social life, political fight and interstate relations of Khiva Khanate.